2013
DOI: 10.1037/a0030886
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drinking goal on treatment outcome for alcoholism.

Abstract: Objective It is well known to clinicians and researchers in the field of alcoholism that patients vary with respect to drinking goal. The objective of this study is to elucidate the contribution of drinking goal to treatment outcome in the context of specific behavioral and pharmacological interventions. Method Participants were 1226 alcohol dependent individuals enrolled in a large, multi-site trial of Combined Behavioral Intervention (CBI), acamprosate, and naltrexone. Drinking goal was coded as follows: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 46 publications
3
55
1
2
Order By: Relevance
“…That is, patients with a goal of abstinence may be more responsive to alcohol use disorder treatment in a primary care setting, 14 which seems to be the case in alcohol treatment settings as well. 13,[15][16][17] It should also be noted that pretreatment alcohol use seems to be associated with pretreatment drinking goal. Both frequent and nearly daily drinkers versus consistent daily drinkers were more likely to select a goal of abstinence; yet, based on our growth curve models, consistent daily drinkers with a goal of abstinence made significantly notable gains in PDA, which may be a counterintuitive finding given the frequency of drinking among participants in this trajectory class.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, patients with a goal of abstinence may be more responsive to alcohol use disorder treatment in a primary care setting, 14 which seems to be the case in alcohol treatment settings as well. 13,[15][16][17] It should also be noted that pretreatment alcohol use seems to be associated with pretreatment drinking goal. Both frequent and nearly daily drinkers versus consistent daily drinkers were more likely to select a goal of abstinence; yet, based on our growth curve models, consistent daily drinkers with a goal of abstinence made significantly notable gains in PDA, which may be a counterintuitive finding given the frequency of drinking among participants in this trajectory class.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In other studies of alcohol-dependent or alcohol-abusing individuals, mostly in alcohol treatment settings but also in primary care-only settings, investigators found associations between a drinking goal of abstinence and improved alcohol use outcomes. [13][14][15][16][17] Finally, although not in a purely primary care setting, a trajectory-based investigation of alcohol use before treatment assignment among alcohol-dependent individuals revealed that very frequent drinkers, defined as a 75% probability of any alcohol use on a given day, benefited from acamprosate in that they were more likely to abstain from heavy drinking during the past 2 months of treatment. 18 In that same investigation, very frequent drinkers also benefited from the medication naltrexone in that they were more likely to be continuously abstinent.…”
mentioning
confidence: 99%
“…Consequently, the strength of research evidence is rated as low. However, secondary analyses of clinical trial data show that patient-stated goals of abstinence at study initiation are associated with more days abstinent and greater reductions in alcohol consumption than patient-stated goals of reduced alcohol use (Adamson et al 2010;Al-Otaiba et al 2008;Berger et al 2016;Bujarski et al 2013;Chang et al 2006;Dunn and Strain 2013;Gueorguieva et al 2014;Meyer et al 2014;Mowbray et al 2013). In addition, patient goals sometimes changed in the course of treatment.…”
Section: Statement 5: Determination Of Initial Treatment Goalsmentioning
confidence: 99%
“…На прогноз ремиссии также оказывает влияние длительность противоалкогольной терапии (так, при лечебном курсе длительностью до 3 месяцев последу-ющие ремиссии обычно более продолжительны, чем при краткосрочной терапии около 1 месяца), а также регулярность и длительность (многие годы) поддер-живающей терапии [11,13,33,39,41]. В достижении ремиссии при алкогольной зависимости большую роль отводят установке пациента на полный отказ от спиртного [11,33], вере пациента в возможность до-стижения поставленной цели и готовность работы над этой целью [38,39].…”
Section: Psychology and Psychiatryunclassified
“…В достижении ремиссии при алкогольной зависимости большую роль отводят установке пациента на полный отказ от спиртного [11,33], вере пациента в возможность до-стижения поставленной цели и готовность работы над этой целью [38,39]. В первый год отказа от алкоголя среди лечебных мероприятий ведущими являются поддержание установки на трезвость, лечение им-пульсивности, депрессии, социальная поддержка [36].…”
Section: Psychology and Psychiatryunclassified